DAMPAK PERSEPSI PENTINGNYA ISU SOSIAL DAN PUBLIKASI NEGATIF TERHADAP DUGAAN DUKUNGAN STARBUCKS TERHADAP ISRAEL DALAM KONFLIK GAZA TERHADAP KEPUTUSAN PEMBELIAN PELANGGAN DI MANADO - Edward T. B. Kamoda ,; Lawren J. Rumokoy ,; Ferdinand J. Tumewu ,; Maya P. Warouw, (Juremi: Jurnal Riset Ekonomi, 2025)
This study examines how the perceived importance of social issues and negative publicity regarding Starbucks' alleged support for Israel in the Gaza conflict affect customer purchase decisions in Manado, Indonesia. A quantitative approach was used, with 100 respondents selected via stratified random sampling. The results show that while the perceived importance of social issues does not significantly impact purchase decisions, negative publicity has a strong and significant influence. Moreover, the combined effect of these factors significantly affects consumer behavior. These findings emphasize the power of negative publicity in shaping purchasing decisions, particularly in contexts involving politically sensitive issues. The study provides insights for businesses on how social and political narratives can influence consumer choices in emerging markets.